Changing Cultures European Perspectives on the History of Portland Cement and Reinforced Concrete, 19th and 20th Centuries - Mascarenhas Mateus, João (Taylor & Francis, 2023)
The construction practices we employ in our daily life in European societies today were shaped by major changes in the past, such as the introduction and dissemination of Portland cement and reinforced concrete, a development that constitutes a fundamental chapter in the history of construction in the 19th and 20th centuries. Such changes were boosted by several innovations in the fields of applied mathematics, chemistry and physics. They involved patents licensing, optimization of materials production and machinery. There were new legislative frameworks, a specific knowledge transfer within a network of actors and the transformation of hierarchical frameworks. Written by international specialists, this two-part book is centred on case studies from the UK, Germany, Switzerland, France, Belgium, Portugal, Spain and Italy. The first part explores the mutual international influence between these countries and their intrinsic characteristics in this field, resulting from each nation's particular economic, social, political, cultural and technological conditions. The second part focuses on the history of public works companies. Capable of carrying out both private works and major infrastructures, these players exemplify the technological and business advances that the construction sector has experienced over the last two centuries. This book is a must-read for researchers on contemporary construction history in Europe. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Create Commons Attribution-Non Commercial-No Derivatives 4.0 (CC-BY-NC-ND) license.